2007
DOI: 10.1016/j.jinorgbio.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair glycosylases with a [4Fe–4S] cluster: A redox cofactor for DNA-mediated charge transport?

Abstract: The [4Fe-4S] cluster is ubiquitous to a class of base excision repair enzymes, in organisms ranging from bacteria to man, and was first considered as a structural element, owing to its redox stability under physiological conditions. When studied bound to DNA, two of these repair proteins (MutY and Endonuclease III from Escherichia coli) display DNA-dependent reversible electron transfer with characteristics typical of high potential iron proteins. These results have inspired a reexamination of the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 79 publications
1
44
0
Order By: Relevance
“…The bacterial DinG helicase is active only when its H 2 O 2 -resistant cluster is oxidized (50). In the case of the base excision repair enzymes, it was shown that oxidized MutY has a greater affinity for DNA and that DNAbound MutY can be reduced by another distally bound MutY through DNA-mediated charge transfer (51). Thus, all known Fe-S proteins that control their activity through the redox state of the Fe-S cluster are involved in the cellular response after an oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial DinG helicase is active only when its H 2 O 2 -resistant cluster is oxidized (50). In the case of the base excision repair enzymes, it was shown that oxidized MutY has a greater affinity for DNA and that DNAbound MutY can be reduced by another distally bound MutY through DNA-mediated charge transfer (51). Thus, all known Fe-S proteins that control their activity through the redox state of the Fe-S cluster are involved in the cellular response after an oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…DNA binding thus changes the redox properties of the enzymes from being similar to ferredoxins to instead resembling high potential iron proteins. Based on these data, we have proposed a redox role for the [4Fe-4S] clusters in long-range DNA-mediated signaling as a first step in detecting damaged sites that are to be repaired in the genome (32)(33)(34)38). Our ability to alter the redox states of these proteins in a DNA-mediated manner further suggests that DNA may be a medium through which oxidation/ reduction reactions occur.…”
mentioning
confidence: 86%
“…For this purpose, we have utilized noncovalent 104,105,110-116 and covalent 106,117-125 redox probes as well as DNA-binding proteins that are redox-active. 126-133 These different probes are illustrated in Fig. 4.…”
Section: Dna Ct On Surfacesmentioning
confidence: 99%